2006
DOI: 10.1111/j.1365-2966.2006.10117.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of HD molecules in merging dark matter haloes

Abstract: HD molecules can be an important cooling agent of the primordial gas behind the shock waves originated through mergings of the dark matter haloes at epochs when first luminous objects were to form. We study the necessary conditions for the HD cooling to switch on in the low temperature range $T<200$ K. We show that these conditions are fulfiled in merging haloes with the total (dark matter and baryon) mass in excess of $M_{\rm cr}\sim 10^7[(1+z)/20]^{-2}\msun$. Haloes with masses $M>M_{\rm cr}$ may be the site… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 53 publications
1
54
3
Order By: Relevance
“…An additional effect of the merger could be that the shock-induced electron fraction enhances the cooling. This mechanism was initially proposed by Shchekinov & Vasiliev (2006) and Prieto et al (2014), and recently confirmed by a numerical simulation in the absence of radiative backgrounds (Bovino et al 2014).…”
Section: Cosmological Scenariomentioning
confidence: 66%
“…An additional effect of the merger could be that the shock-induced electron fraction enhances the cooling. This mechanism was initially proposed by Shchekinov & Vasiliev (2006) and Prieto et al (2014), and recently confirmed by a numerical simulation in the absence of radiative backgrounds (Bovino et al 2014).…”
Section: Cosmological Scenariomentioning
confidence: 66%
“…In this scenario, the merging of multiple dark matter haloes induces the formation of shockwaves in which HD formation is enhanced. Such merging often yields large mass haloes with M halo > 10 7 [(1 + z)/20] −2 M ⊙ (Shchekinov & Vasiliev 2006), whereas our HD-cooling clouds are found in lower mass haloes with ∼ 5 × 10 5 M ⊙ at z ∼ 10 − 16.…”
Section: Jeans Scale: Gravitationally Unstable Cloudsmentioning
confidence: 79%
“…fHD/fH 2 increases sharply in the density range 10 6 cm −3 < nH,cen < 10 7 cm −3 and eventually exceeds 10 −3 . We classify our 1540 samples of primordial clouds as one of three possible cases, depending on fHD/fH 2 during the collapse: H2-cooling cases (1186 cases), HD-cooling cases (151), and the intermediate cases (203), where the numbers 6 Another possible route for HD-cooling primordial starformation is suggested by some studies (Uehara & Inutsuka 2000;Shchekinov & Vasiliev 2006;Prieto et al 2012;Bovino et al 2014;Prieto et al 2014). In this scenario, the merging of multiple dark matter haloes induces the formation of shockwaves in which HD formation is enhanced.…”
Section: Jeans Scale: Gravitationally Unstable Cloudsmentioning
confidence: 99%
“…HD cooling is also of great importance in situations where an increase in the fractional ionization of the gas has led to an increase in the H 2 fraction. In this situation, the gas often becomes cool enough for HD to dominate (see e.g., Nakamura & Umemura 2002;Nagakura & Omukai 2005;Johnson & Bromm 2006;Shchekinov & Vasiliev 2006). This scenario is discussed in more detail in §3.4 below.…”
Section: Are We Including All Of the Significant Coolants?mentioning
confidence: 99%